2006
DOI: 10.1055/s-2006-921416
|View full text |Cite
|
Sign up to set email alerts
|

Auswirkungen der Entnahme des mittleren Patellarsehnendrittels auf die Kinematik des Kniegelenkes und den retropatellaren Druck

Abstract: The shortening of the patellar tendon due to tendon removal, as already suggested in several previous studies, is not attributed to the removal of the central portion of the tendon itself, but more likely due to secondary scarring contraction of the tissue. The changes of the patellarkinematics and the retropatellar pressure observed in this study are probably not of any clinical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…The purpose of our examination of Tekscan sensors was to prepare a series of experiments on changes in retropatellar pressure and force distribution after knee joint surgeries [810]. Prior to our studies, there were only a few publications which reported retropatellar pressure measurements using the Tekscan sensors for dynamic measurements [1114].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of our examination of Tekscan sensors was to prepare a series of experiments on changes in retropatellar pressure and force distribution after knee joint surgeries [810]. Prior to our studies, there were only a few publications which reported retropatellar pressure measurements using the Tekscan sensors for dynamic measurements [1114].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, we performed a series of experiments to determine the optimal retropatellar implantation method as well as to detect possible sources of error when using Tekscan sensors. A further purpose was to record and quantify possible sensor wear in order to account for bias wear might cause in further studies which were planned [8]. …”
Section: Introductionmentioning
confidence: 99%